2023
DOI: 10.1186/s12951-022-01755-5
|View full text |Cite
|
Sign up to set email alerts
|

Tea leaf-derived exosome-like nanotherapeutics retard breast tumor growth by pro-apoptosis and microbiota modulation

Abstract: While several artificial nanodrugs have been approved for clinical treatment of breast tumor, their long-term applications are restricted by unsatisfactory therapeutic outcomes, side reactions and high costs. Conversely, edible plant-derived natural nanotherapeutics (NTs) are source-widespread and cost-effective, which have been shown remarkably effective in disease treatment. Herein, we extracted and purified exosome-like NTs from tea leaves (TLNTs), which had an average diameter of 166.9 nm and a negative-ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 52 publications
0
26
0
Order By: Relevance
“…Betker et al [ 29 ] and Samuel et al [ 28 ] also show that orally ingested sEVs can migrate and accumulate in xenograft tumors in vivo. Other sources of sEVs studied in similar investigations are those obtained from yeast [ 28 ], beer [ 28 ], grape [ 34 ], acerola [ 33 ], ginger [ 32 ], garlic [ 35 ], tea leaves [ 36 ], and mulberry bark [ 37 ]. Yeast-, grape-, acerola-, ginger-, garlic-, tea leaves- and mulberry bark-derived sEVs showed a biodistribution pattern like that previously described for cow’s milk-derived sEVs, but beer-derived sEVs in the mouse’s organs could not be detected [ 28 ].…”
Section: Biodistribution Stability and Safety Of Oral Delivery Of Nat...mentioning
confidence: 99%
See 1 more Smart Citation
“…Betker et al [ 29 ] and Samuel et al [ 28 ] also show that orally ingested sEVs can migrate and accumulate in xenograft tumors in vivo. Other sources of sEVs studied in similar investigations are those obtained from yeast [ 28 ], beer [ 28 ], grape [ 34 ], acerola [ 33 ], ginger [ 32 ], garlic [ 35 ], tea leaves [ 36 ], and mulberry bark [ 37 ]. Yeast-, grape-, acerola-, ginger-, garlic-, tea leaves- and mulberry bark-derived sEVs showed a biodistribution pattern like that previously described for cow’s milk-derived sEVs, but beer-derived sEVs in the mouse’s organs could not be detected [ 28 ].…”
Section: Biodistribution Stability and Safety Of Oral Delivery Of Nat...mentioning
confidence: 99%
“…In global terms, the biological effect reported for FDVs is highly associated with the source of identification. However, comparing articles is challenging since different isolation methods are employed, the doses administrated are different, and several routes of administration are tested [ 36 , 64 ].…”
Section: Food Derived Vesicles (Fdvs)-based Nutraceutical Perspective...mentioning
confidence: 99%
“…225 Furthermore, the authors also manifested that the intravenous injection administration of TFENs induced evident hepatorenal toxicity and immune activation compared with oral administration, which showed the great potential of TFENs as oral therapeutic platforms for the treatment of breast cancer. 226 To reduce the clearance rate by the mononuclear phagocytic system, mPEG2000-TK-CP05 decorated exosomes that contain RB (photosensitizer Rose Bengal) and Dox (Doxorubicin) were constructed by Wan et al for enhanced chemo/photodynamic therapy by prolonging exosomal blood circulation and accumulation in the tumor region. These engineered exosomes were called Stealth Exo, which not only improved the accessibility and efficiency of drug delivery but also minimized the side effects of Dox and enhanced antitumor immune responses in cancer treatment.…”
Section: Protein Deliverymentioning
confidence: 99%
“…Chen et al reported that natural exosome-like nanoplatform from tea flowers (TFENs) could promote ROS amplification to trigger mitochondrial damage in cancer cells, which are mainly responsible for the inhibition of the growth and metastasis of breast cancer . Furthermore, the authors also manifested that the intravenous injection administration of TFENs induced evident hepatorenal toxicity and immune activation compared with oral administration, which showed the great potential of TFENs as oral therapeutic platforms for the treatment of breast cancer …”
Section: Exosome-like Nanovectors For Cancer Therapymentioning
confidence: 99%
“…The engineered KPEVs were stably absorbed into the gastric adenocarcinoma (AGS) cells, leading to the suppression of cell viability in a dose-dependent manner [ 60 ]. Other interesting findings were the identification of exosome-like nanotherapeutics from tea flowers [ 61 ] and tea leaves [ 62 ]. The cellular experiments indicated strong cytotoxicity effects of these exosome-like nanotherapeutics against breast cancer cells in vivo and in vitro.…”
Section: Introductionmentioning
confidence: 99%